2005
DOI: 10.4269/ajtmh.2005.73.166
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Efficacy of Antifolate Antimalarial Therapy by Folic Acid Supplementation

Abstract: Malaria and anemia are common conditions in patients presenting to outpatient clinics in Kenya. Anemia is usually due to malaria infection with underlying micronutrient deficiency. Iron therapy has been shown to enhance recovery from anemia in children with malaria, without affecting malaria treatment. Iron and folic acid are often prescribed together for anemic individuals. Until recently in Kenya, the drug of first choice for non-severe malaria was sulfadoxine-pyrimethamine (SP), an antifolate antimalarial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…In Kenyan patients treated for falciparum malaria with sulfadoxine‐pyrimethamine, daily supplementation with folic acid (2·5 or 5 mg for those aged <2 and ≥2 years, respectively) reduced the time to treatment failure as assessed by parasitological examination of blood slides collected at various points of follow‐up (Carter et al , 2005). There was no evidence of an effect on recovery from anaemia.…”
Section: Increased Folate Intake and Malariamentioning
confidence: 99%
“…In Kenyan patients treated for falciparum malaria with sulfadoxine‐pyrimethamine, daily supplementation with folic acid (2·5 or 5 mg for those aged <2 and ≥2 years, respectively) reduced the time to treatment failure as assessed by parasitological examination of blood slides collected at various points of follow‐up (Carter et al , 2005). There was no evidence of an effect on recovery from anaemia.…”
Section: Increased Folate Intake and Malariamentioning
confidence: 99%
“…These include masking of vitamin B 12 deficiency primarily in elderly [58]; decreased natural killer cell cytotoxicity [56]; resistance to antifolate drugs used against arthritis [59][60][61], malaria [62], and cancer [63,64]; an increased risk of insulin resistance and obesity and asthma in children born to folic acid-supplemented mothers [65]; accelerated progression of diabetic nephropathy [66]; an increased risk of cognitive impairment in elderly with suboptimal vitamin B 12 status [67,68]; aberrant patterns and dysregulation of DNA methylation [69]; and the promotion of progression of existing precancerous lesions or cancer [1,2,15,16].…”
Section: Potential Adverse Effects Of Folic Acid Supplementationmentioning
confidence: 99%
“…Gene amplification was demonstrated as a potential sulfonamide drug resistance mechanism in model systems [22,23] and recently shown to be a clinically valid resistance mechanism following chromosomal amplification of genetic elements encoding DHPS in S. agalactieae [24]. The competing effect of increased levels of the DHPS substrate pABA was shown to confound the effects of sulfonamides [2] both clinically and in model systems [25] as was the acquisition of environmental folates [26,27]. Drug resistance mutations have long been known to confer a fitness compromise.…”
Section: Antifolate Drug Resistance Mechanismsmentioning
confidence: 99%
“…It has been demonstrated that antimalarial therapy using antifolates can be significantly compromised by the concomitant dietary supplementation of folic acid [26,27]. In addition, increased expression levels of DHPS increase or decrease sulfa drug resistance depending on whether pABA is high or low, respectively [22,28].…”
Section: Plasmodium Falciparummentioning
confidence: 99%